The challenge of targeting toxins to tumors - Seon, Ben (Henry Stewart Talks, 2007)
Generation of immunotoxins, Mode of action of different immunotoxins, Strategies to overcome the major impediments in the therapeutic application of immunotoxins to cancer patients, Anti-endoglin monoclonal antibodies and immunotoxins, Anti-angiogenic therapy of tumors, Vascular targeting therapy of tumors, Comparison between immunotoxins and naked antibodies in therapeutic application
Archived at 2021/02/25